1993
DOI: 10.1109/23.273462
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of heavy ion charge generation and collection dynamics

Abstract: This paper describes a complete simulation approach to investigating the physics of heayy-ion charge generation and collection during a single event transient in a PN diode. The simulations explore the effects of Werent ion track models, applied biases, background dopings, and LET on the transient responses of a PN diode. The simulation results show that ion track structure and charge collection via diffusiondominated processes play important roles in determining device transient responses. The simulations sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Previous works have demonstrated that the different charge generation distributions used for the radial ion track does affect the device transient response, but the variation is typically limited to ~5% for ion strikes on bulk p-n diodes (Dodd, 2005;Dussault et al, 1993). Considering a LET which is not constant with depth along the path has a more significant impact on the transient response in bulk devices.…”
Section: Modeling the Effect Of A Particle Strikementioning
confidence: 99%
See 2 more Smart Citations
“…Previous works have demonstrated that the different charge generation distributions used for the radial ion track does affect the device transient response, but the variation is typically limited to ~5% for ion strikes on bulk p-n diodes (Dodd, 2005;Dussault et al, 1993). Considering a LET which is not constant with depth along the path has a more significant impact on the transient response in bulk devices.…”
Section: Modeling the Effect Of A Particle Strikementioning
confidence: 99%
“…Considering a LET which is not constant with depth along the path has a more significant impact on the transient response in bulk devices. The key parameters of the single event transient (peak current, time to peak and collected charge) have up to 20% variation when LET is allowed to vary with depth compared to the case of a constant LET (Dussault et al, 1993). Nevertheless, the LET variation with depth has no influence on the transient response of actual SOI devices with thin Silicon film.…”
Section: Modeling the Effect Of A Particle Strikementioning
confidence: 99%
See 1 more Smart Citation
“…Carrier concentrations above 10 cm-3 can extend to radii of more than a micron within a highenergy heavy ion track such as the 1.7 GeV 197Au and 1. 9 GeV 1271 ions used in this research [1,2]. Additionally, highenergy heavy ions have sufficient ranges to penetrate deep within a device, creating potentially conductive paths through regions of the device usually isolated during normal operation.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most interesting models is the "non-uniform 75 power law" track model, based on the Katz theory (Kobetich & Katz, 1968) and developed by Stapor (Stapor & McDonald, 1988). In this model, the ion track has a radial distribution of excess carriers expressed by a power law distribution and allows the charge density to vary along the track (Dussault et al, 1993). Other analytical models propose constant radius nonuniform track or Gaussian distribution non-uniform track.…”
Section: Modeling the Effect Of A Particle Strikementioning
confidence: 99%